Comparation of time-course, dose-effect, influencing factors and adverse events of biologics in the treatment of adults with moderate to severe plaque psoriasis - Gao, Weiqi; Yu, Boran; Yan, Ya; Zhao, Libo; Zhao, Rongsheng (Frontiers in Immunology, 2023)
Biologics used to treat moderate to severe plaque psoriasis (MSPP) represent one of the most significant therapeutic advancements in the field of dermatology. Up to now, the relative efficacy and safety across approved and investigational biologics for MSPP remains unclear. The objective of this study was to quantify the relative efficacy of various biological treatments for MSPP measured by PASI75, PASI90 and PASI100 (The proportion of patients whose Psoriasis Area and Severity Index score (PASI) decreased by ≥ 75%, 90% and 100% compared with baseline, respectively). In addition, random models were used together with a Bayesian method to compare direct and indirect Adverse Events (AEs) of biologics with placebo, to make probabilistic statements and predictions on their AEs. The analysis dataset was composed of summary-level data from 54 trials, containing 27,808 patients, with treatment of 17 drugs. Three mathematical models with nonparametric placebo estimations were developed to describe the longitudinal profile for the above three efficacy measures. The results detected significant differences among included treatments, in brief, bimekizumab, sonelokimab and ixekizumab treatments were the most effective treatments among the biologics. The effects of covariate were further evaluated, patients’ age, body weight, duration of disease and percentage of patients previously treated with a biological therapy showed impact on the efficacy. In addition, we found that ixekizumab and risankizumab performed relatively stable with respect to efficacy and safety.